Patterns of use of the Mental Health Act 1983, from 2007–2008 to 2016–2017, in two major London secondary mental healthcare providers. Issue 6 (November 2019) - Oram, Sian; Colling, Craig; Pritchard, Megan; Khondoker, Mizanur; Fonseca de Freitas, Daniela; Ter-Minassian, Lucile; Downs, Johnny; Lloyd-Evans, Brynmor; Markham, Sarah; Werbeloff, Nomi; Chang, Chin-Kuo; Johnson, Sonia; et al.
Summary: Trends in detention under the Mental Health Act 1983 in two major London secondary mental healthcare providers were explored using patient-level data in a historical cohort study between 2007–2008 and 2016–2017. An increase in the number of detention episodes initiated per fiscal year was observed at both sites. The rise was accompanied by an increase in the number of active patients; the proportion of active patients detained per year remained relatively stable. Findings suggest that the rise in the number of detentions reflects the rise of the number of people receiving secondary mental healthcare.